Endothelial Function in Healthy Young Individuals Is Associated with Dietary Consumption of Saturated Fat - Lambert, Elisabeth A.; Phillips, Sarah; Belski, Regina; Tursunalieva, Ainura; Eikelis, Nina; Sari, Carolina I.; Dixon, John B.; Straznicky, Nora; Grima, Mariee; Head, Geoffrey A.; Schlaich, Markus; Lambert, Gavin W. (Frontiers in Physiology, 2017)
Background: A diet rich in fat, in particular saturated fat (SF), may be linked to cardiovascular disease development, possibly due to a detrimental effect of fat on endothelial function (EF). Objective: We aimed to determine whether the habitual SF intake [as a ratio to total fat (the sum of saturated, polyunsaturated and monounsaturated fat)] might influence endothelial function in young, overweight but otherwise healthy adults. Design: Sixty-nine young adults (49 males, mean age: 23±1 years, mean BMI: 29.1±0.8 kg/m2) were classified into three tertiles according to their habitual SF intake consumption (low SF: <39%, medium SF 39.1-43.7% and high SF: >43.7% of total fat). Endothelial function was assessed using digital amplitude tonometry. Results: The three groups of individuals were comparable for total energy intake and calories from: fat, protein and carbohydrates. There was no difference in anthropometric and hemodynamic variables among the groups. Those in the high SF group presented with impaired endothelial function [reactive hyperemia index (RHI): high SF: 1.60± 0.08 compared to 2.23±0.16 in the medium SF and 2.12±0.14 in the low SF group, P<0.01]. Regression analysis, including gender, age, ethnicity, body mass index indicated that the ratio of SF to total fat was an independent predictor of the RHI (P<0.05). Conclusion: The habitual consumption of a diet high in SF in relation to polyunsaturated and monounsaturated fat was strongly associated with impaired endothelial function in young overweight adults, potentially contributing to increased risk of developing cardiovascular disease.